(untitled) (Bangladesh Journal of Medical Science, 2021)
Background: Proper diagnosis and treatment planning are the first steps in management of bilateral impacted maxillary canines (BIMC). Case Presentation: A 14 years old Saudi female patient with Class II subdivision right molar relationship and BIMC managed by comprehensive orthodontic treatment. Conclusion: A well-balanced occlusion by orthodontic management of the case has been done. Bangladesh Journal of Medical Science Vol.20(1) 2021 p.212-215